Clinical Outcomes of Hip Arthroscopic Surgery in Patients With Femoral Retroversion: A Matched Study to Patients With Normal Femoral Anteversion. Issue 10 (27th October 2017) - Hartigan, David E.; Perets, Itay; Walsh, John P.; Chaharbakhshi, Edwin O.; Yuen, Leslie C.; Domb, Benjamin G.
Background: Femoral retroversion has been noted as a possible risk factor for poor clinical results after hip arthroscopic surgery. Purpose: To compare the outcomes of the arthroscopic treatment of hip abnormalities in patients with femoral retroversion to patients with femoral anteversion between 10° and 20°. Study Design: Cohort study; Level of evidence, 3. Methods: Between November 2011 and September 2013, 790 hip arthroscopic procedures were performed at a single institution. Of these, 59 hips (7.5%) were located in patients with femoral version ≤0°, calculated using preoperative magnetic resonance imaging. These patients were pair matched, based on body mass index ±5 kg/m 2, age ±5 years, and Tönnis grade, with 59 patients with femoral anteversion between 10° and 20°. Exclusion criteria included Perthes disease, inflammatory arthritis, slipped capital femoral epiphysis, previous hip surgery, abductor repair, lateral center-edge angle <20°, Tönnis grade >1, and acetabular profunda or protrusio. Patient-reported outcomes (PROs) were recorded preoperatively, at 3 months postoperatively, and annually thereafter. The PROs utilized were the modified Harris Hip Score (mHHS), Non-Arthritic Hip Score (NAHS), and Hip Outcome Score–Sports-Specific Subscale (HOS-SSS). The visual analog scale (VAS) was collected to assess the patients' pain; patient satisfaction scores (0-10) were also collected. Radiographs were collected at the above time intervals as well. Results: Two patients from the control group and 1 patient from the retroverted group required total hip arthroplasty at a mean 19.5 and 26.3 months, respectively. Both groups demonstrated significant improvement from their preoperative state in all PRO and VAS scores ( P < .001). No differences in preoperative, postoperative, or change in PRO and VAS scores between the groups were noted. Conclusion: Patients with femoral retroversion reported similar outcomes compared to patients with normal femoral version when undergoing hip arthroscopic surgery. Both groups had similar improvements from the preoperative state.